2012
DOI: 10.1104/pp.112.199380
|View full text |Cite
|
Sign up to set email alerts
|

An A/ENTH Domain-Containing Protein Functions as an Adaptor for Clathrin-Coated Vesicles on the Growing Cell Plate in Arabidopsis Root Cells    

Abstract: Cytokinesis is the process of partitioning the cytoplasm of a dividing cell, thereby completing mitosis. Cytokinesis in the plant cell is achieved by the formation of a new cell wall between daughter nuclei using components carried in Golgi-derived vesicles that accumulate at the midplane of the phragmoplast and fuse to form the cell plate. Proteins that play major roles in the development of the cell plate in plant cells are not well defined. Here, we report that an AP180 amino-terminal homology/epsin amino-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
62
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 61 publications
7
62
0
1
Order By: Relevance
“…As none of the clathrin isoforms were retrieved in the TAP experiments, we tested whether AP-2 interacted with clathrin in vivo by performing coimmunoprecipitation experiments in Arabidopsis seedlings expressing CLC2-GFP (Konopka et al, 2008). Protein gel blot analysis with an antibody directed against the two AP2A proteins (Song et al, 2012) revealed that AP2A coimmunoprecipitated with CLC2-GFP ( Figure 2B). Additional BiFC experiments validated that AP2A1 and clathrin (CLC2 and CHC) interacted with a GFP signal localized at the PM, in agreement with the coimmunoprecipitation data ( Figure 2C; see Supplemental Table 2 and Supplemental Figure 2 online).…”
Section: Isolation Of the Arabidopsis Ap-2 Complexmentioning
confidence: 99%
“…As none of the clathrin isoforms were retrieved in the TAP experiments, we tested whether AP-2 interacted with clathrin in vivo by performing coimmunoprecipitation experiments in Arabidopsis seedlings expressing CLC2-GFP (Konopka et al, 2008). Protein gel blot analysis with an antibody directed against the two AP2A proteins (Song et al, 2012) revealed that AP2A coimmunoprecipitated with CLC2-GFP ( Figure 2B). Additional BiFC experiments validated that AP2A1 and clathrin (CLC2 and CHC) interacted with a GFP signal localized at the PM, in agreement with the coimmunoprecipitation data ( Figure 2C; see Supplemental Table 2 and Supplemental Figure 2 online).…”
Section: Isolation Of the Arabidopsis Ap-2 Complexmentioning
confidence: 99%
“…Plant genomes also encode many clathrin-associated sorting proteins (CLASPs) that aid adaptin-mediated formation of CCVs, including AP180/ epsin N-terminal homology (A/ENTH) domain proteins and dynamin-related proteins (DRPs) that facilitate membrane curvature and vesicle scission, respectively (Chen et al, 2011). Clathrin, A/ENTH domain proteins, DRPs, and the adaptin-related TPLATE have also been detected at the CP (Konopka and Bednarek, 2008a;Konopka et al, 2008;Fujimoto et al, 2010;Van Damme et al, 2011;Ito et al, 2012;Song et al, 2012), suggesting that a mechanism similar to CME and clathrin-mediated membrane retrieval at the TGN facilitates membrane recycling from the CP during plant cytokinesis.…”
Section: Introductionmentioning
confidence: 99%
“…GFP-tagged ECA1 (AT2G01600), ECA2 (AT1G03050), and ECA4 (AT2G25430) (and ECA1-specific antibody signal) localize to the PM and the nascent cell plate and to some extent to punctate structures (Figure 3). In the case of ECA1, these punctae were further identified as EEs, mainly via colocalization with early endocytosed FM4-64 and colocalization also after treatment with Brefeldin A (BFA; Song et al, 2012). Analysis of spatiotemporal dynamics of ECA1 labeling at the nascent cell plate revealed a pattern that is suggestive of a role in endocytosis from the forming cell plate (reviewed in Jürgens, 2005).…”
Section: Anths: a Large Group Involved In Endocytosismentioning
confidence: 99%
“…For another three ANTH proteins, involvement in CCV formation at the cell plate has been postulated (Song et al, 2012). GFP-tagged ECA1 (AT2G01600), ECA2 (AT1G03050), and ECA4 (AT2G25430) (and ECA1-specific antibody signal) localize to the PM and the nascent cell plate and to some extent to punctate structures (Figure 3).…”
Section: Anths: a Large Group Involved In Endocytosismentioning
confidence: 99%